Qualität im Fokus – Measuring the Quality of Prison Life: Impressionen aus der Zusammenarbeit im Modellversuch «Soziales Klima im Justizvollzug» - Keller, Annette (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
The project “Social Climate in the Prison System – Measuring the Quality of Prison Life” was the first time the MQPL+ method was used in Switzerland to systematically assess and improve quality in prisons. This article traces the course of the project – from conception to implementation – and discusses key findings from a practical perspective, using the Hindelbank prison as a case study. It argues for institutionally anchored quality development in the prison system and emphasizes the importance of continuous reflection and cooperation between practitioners and researchers. (machine translation)